Tras un denário imitativo de Turiasu hallado en Vila Real (Portugal) - Martinez Chico, David (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2017)
The paper shows the isolated discovery of an important Iberian denarius from northem Portugal. The coin is characterized by being covered or a fake coin of the period and presenting an imitative art from Turiasu. Several reflexions and new numismatic material about the covered denarii, imitatives, hybrids and brockages also offered.